Millimetre-Wave Planar Phased Patch Array with Sidelobe Suppression for High Data-Rate Transmission - Hung-Chen Chen; Tsenchieh Chiu; Ching-Luh Hsu (International Journal of Antennas and Propagation)
A design of 38 GHz planar phased patch array with sidelobe suppression for data-rate enhancement is proposed in the paper. The proposed array is formed of three 24-element subarrays of patches. Each patch has its own transmit/receive modules (TRM) consisting of a digitally controlled attenuator and phase shifter. In order to achieve high data-rate communications, the noise, especially due to the undesired signals received from the sidelobes, should be reduced with high sidelobe suppression of subarray. The sidelobe suppression of the proposed subarray is first improved to 17.92 dB with a diamond-shaped aperture and then better than 35 dB with a tapered radiation power distribution. The excellent sidelobe suppression of the antenna array is essential for the beam-division multiplexing applications when the signal sources are close to each other. The proposed design is validated experimentally, including the data-rate measurements showing that the 7 Gbps data transmission can be achieved with sufficient sidelobe suppression of the proposed design.